Difference between revisions of "009B Sample Midterm 3, Problem 5"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam">Evaluate the indefinite and definite integrals. ::<span class="exam">a) <math>\int \tan^3x ~dx</math> ::<span class="exam">b) <math>\int_0^\pi \sin^2x~dx<...")
 
Line 1: Line 1:
 
<span class="exam">Evaluate the indefinite and definite integrals.
 
<span class="exam">Evaluate the indefinite and definite integrals.
  
::<span class="exam">a) <math>\int \tan^3x ~dx</math>  
+
<span class="exam">(a) &nbsp; <math>\int \tan^3x ~dx</math>  
::<span class="exam">b) <math>\int_0^\pi \sin^2x~dx</math>
+
 
 +
<span class="exam">(b) &nbsp; <math>\int_0^\pi \sin^2x~dx</math>
  
  
Line 8: Line 9:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|Recall the trig identities:  
+
|'''1.''' Recall the trig identity
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -3px">\tan^2x+1=\sec^2x</math>
 
|-
 
|-
|'''1.''' <math style="vertical-align: -3px">\tan^2x+1=\sec^2x</math>
+
|'''2.''' Recall the trig identity
 
|-
 
|-
|'''2.''' <math style="vertical-align: -13px">\sin^2(x)=\frac{1-\cos(2x)}{2}</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">\sin^2(x)=\frac{1-\cos(2x)}{2}</math>
 
|-
 
|-
|How would you integrate <math style="vertical-align: -1px">\tan x~dx?</math>
+
|'''3.''' How would you integrate &nbsp;<math style="vertical-align: -1px">\tan x~dx?</math>
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: 0px">u</math>-substitution. First, write <math style="vertical-align: -14px">\int \tan x~dx=\int \frac{\sin x}{\cos x}~dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; You could use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; First, write &nbsp;<math style="vertical-align: -14px">\int \tan x~dx=\int \frac{\sin x}{\cos x}~dx.</math>
 
|-
 
|-
 
|
 
|
::Now, let <math style="vertical-align: -5px">u=\cos(x).</math> Then, <math style="vertical-align: -5px">du=-\sin(x)dx.</math> Thus,  
+
&nbsp; &nbsp; &nbsp; &nbsp; Now, let &nbsp;<math style="vertical-align: -5px">u=\cos(x).</math>&nbsp; Then, &nbsp;<math style="vertical-align: -5px">du=-\sin(x)dx.</math>  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Thus,  
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int \tan x~dx} & = & \displaystyle{\int \frac{-1}{u}~du}\\
 
\displaystyle{\int \tan x~dx} & = & \displaystyle{\int \frac{-1}{u}~du}\\
 
&&\\
 
&&\\
Line 31: Line 38:
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 41: Line 49:
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -14px">\int \tan^3x~dx=\int \tan^2x\tan x ~dx.</math>  
+
&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -14px">\int \tan^3x~dx=\int \tan^2x\tan x ~dx.</math>  
 
|-
 
|-
|Since <math style="vertical-align: -5px">\tan^2x=\sec^2x-1,</math> we have  
+
|Since &nbsp;<math style="vertical-align: -5px">\tan^2x=\sec^2x-1,</math>&nbsp; we have  
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int (\sec^2x-1)\tan x ~dx}\\
 
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int (\sec^2x-1)\tan x ~dx}\\
 
&&\\
 
&&\\
Line 56: Line 64:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we need to use <math>u</math>-substitution for the first integral.  
+
|Now, we need to use &nbsp;<math>u</math>-substitution for the first integral.  
 
|-
 
|-
 
|
 
|
::Let <math style="vertical-align: -5px">u=\tan(x).</math> Then, <math style="vertical-align: -1px">du=\sec^2x~dx.</math> So, we have
+
Let &nbsp;<math style="vertical-align: -5px">u=\tan(x).</math>  
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -1px">du=\sec^2x~dx.</math>  
 +
|-
 +
|So, we have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int u~du-\int \tan x~dx}\\
 
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\int u~du-\int \tan x~dx}\\
 
&&\\
 
&&\\
Line 74: Line 86:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
|For the remaining integral, we also need to use <math>u</math>-substitution.  
+
|For the remaining integral, we also need to use &nbsp;<math>u</math>-substitution.  
 
|-
 
|-
 
|First, we write  
 
|First, we write  
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -14px">\int \tan^3x~dx=\frac{\tan^2x}{2}-\int \frac{\sin x}{\cos x}~dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -14px">\int \tan^3x~dx=\frac{\tan^2x}{2}-\int \frac{\sin x}{\cos x}~dx.</math>
 +
|-
 +
|Now, we let &nbsp;<math style="vertical-align: 0px">u=\cos x.</math>
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -1px">du=-\sin x~dx.</math>  
 
|-
 
|-
|Now, we let <math style="vertical-align: 0px">u=\cos x.</math> Then, <math style="vertical-align: -1px">du=-\sin x~dx.</math> So, we get  
+
|Therefore, we get  
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\frac{\tan^2x}{2}+\int \frac{1}{u}~dx}\\
 
\displaystyle{\int \tan^3x~dx} & = & \displaystyle{\frac{\tan^2x}{2}+\int \frac{1}{u}~dx}\\
 
&&\\
 
&&\\
Line 97: Line 113:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|One of the double angle formulas is <math style="vertical-align: -5px">\cos(2x)=1-2\sin^2(x).</math>  
+
|One of the double angle formulas is  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">\cos(2x)=1-2\sin^2(x).</math>  
 
|-
 
|-
|Solving for <math style="vertical-align: -5px">\sin^2(x),</math> we get <math style="vertical-align: -13px">\sin^2(x)=\frac{1-\cos(2x)}{2}.</math>
+
|Solving for &nbsp;<math style="vertical-align: -5px">\sin^2(x),</math>&nbsp; we get  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">\sin^2(x)=\frac{1-\cos(2x)}{2}.</math>
 
|-
 
|-
 
|Plugging this identity into our integral, we get  
 
|Plugging this identity into our integral, we get  
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\int_0^\pi \frac{1-\cos(2x)}{2}~dx}\\
 
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\int_0^\pi \frac{1-\cos(2x)}{2}~dx}\\
 
&&\\
 
&&\\
Line 117: Line 137:
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\left.\frac{x}{2}\right|_{0}^\pi-\int_0^\pi \frac{\cos(2x)}{2}~dx}\\
 
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\left.\frac{x}{2}\right|_{0}^\pi-\int_0^\pi \frac{\cos(2x)}{2}~dx}\\
 
&&\\
 
&&\\
Line 127: Line 147:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
|For the remaining integral, we need to use <math style="vertical-align: 0px">u</math>-substitution.  
+
|For the remaining integral, we need to use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 
|-
 
|-
|Let <math style="vertical-align: -1px">u=2x.</math> Then, <math style="vertical-align: -1px">du=2~dx</math> and <math style="vertical-align: -18px">\frac{du}{2}=dx.</math>  
+
|Let &nbsp;<math style="vertical-align: -1px">u=2x.</math>  
 
|-
 
|-
|Also, since this is a definite integral and we are using <math style="vertical-align: 0px">u</math>-substitution, we need to change the bounds of integration.  
+
|Then, &nbsp;<math style="vertical-align: -1px">du=2~dx</math>&nbsp; and &nbsp;<math style="vertical-align: -18px">\frac{du}{2}=dx.</math>
 
|-
 
|-
|We have <math style="vertical-align: -5px">u_1=2(0)=0</math> and <math style="vertical-align: -5px">u_2=2(\pi)=2\pi.</math>
+
|Also, since this is a definite integral and we are using <math style="vertical-align: 0px">u</math>-substitution,
 +
|-
 +
|we need to change the bounds of integration.
 +
|-
 +
|We have &nbsp;<math style="vertical-align: -5px">u_1=2(0)=0</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">u_2=2(\pi)=2\pi.</math>
 
|-
 
|-
 
|So, the integral becomes
 
|So, the integral becomes
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\frac{\pi}{2}-\int_0^{2\pi} \frac{\cos(u)}{4}~du}\\
 
\displaystyle{\int_0^\pi \sin^2x~dx} & = & \displaystyle{\frac{\pi}{2}-\int_0^{2\pi} \frac{\cos(u)}{4}~du}\\
 
&&\\
 
&&\\
Line 148: Line 172:
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|&nbsp;&nbsp; '''(a)''' <math>\frac{\tan^2x}{2}+\ln |\cos x|+C</math>
+
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math>\frac{\tan^2x}{2}+\ln |\cos x|+C</math>
 
|-
 
|-
|&nbsp;&nbsp; '''(b)''' <math>\frac{\pi}{2}</math>
+
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; <math>\frac{\pi}{2}</math>
 
|}
 
|}
  
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Revision as of 11:21, 9 April 2017

Evaluate the indefinite and definite integrals.

(a)  

(b)  


Foundations:  
1. Recall the trig identity
       
2. Recall the trig identity
       
3. How would you integrate  

        You could use  -substitution.

        First, write  

        Now, let    Then,  

        Thus,

       


Solution:

(a)

Step 1:  
We start by writing

       

Since    we have

       

Step 2:  
Now, we need to use  -substitution for the first integral.

Let  

Then,  
So, we have

       

Step 3:  
For the remaining integral, we also need to use  -substitution.
First, we write

       

Now, we let  
Then,  
Therefore, we get

       

(b)

Step 1:  
One of the double angle formulas is
       
Solving for    we get
       
Plugging this identity into our integral, we get

       

Step 2:  
If we integrate the first integral, we get

       

Step 3:  
For the remaining integral, we need to use  -substitution.
Let  
Then,    and  
Also, since this is a definite integral and we are using -substitution,
we need to change the bounds of integration.
We have    and  
So, the integral becomes

       


Final Answer:  
    (a)    
    (b)    

Return to Sample Exam